2009
DOI: 10.1242/jcs.058263
|View full text |Cite
|
Sign up to set email alerts
|

CaMKIIα interacts with multi-PDZ domain protein MUPP1 in spermatozoa and prevents spontaneous acrosomal exocytosis

Abstract: 2+ -calmodulin releases CaMKII␣ from the PDZ scaffolding protein, MUPP1 represents a central signaling platform to dynamically regulate the assembly and disassembly of binding partners pertinent to acrosomal secretion, thereby precisely adjusting an increase in Ca 2+ to synchronized fusion pore formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 106 publications
1
27
0
Order By: Relevance
“…Streptolysin O (SLO) permeabilization is a widespread methodology used in analysis of dense-core granule exocytosis that we and others have applied to studying the AR (28,(36)(37)(38)(39). This method permits the introduction of exogenous factors-which are not otherwise able to cross membranes-into the cytosol through pores in the plasma membrane generated by SLO.…”
Section: Resultsmentioning
confidence: 99%
“…Streptolysin O (SLO) permeabilization is a widespread methodology used in analysis of dense-core granule exocytosis that we and others have applied to studying the AR (28,(36)(37)(38)(39). This method permits the introduction of exogenous factors-which are not otherwise able to cross membranes-into the cytosol through pores in the plasma membrane generated by SLO.…”
Section: Resultsmentioning
confidence: 99%
“…Chelerythrine, U73122, U73343, Ro-31-7549, adenophostin A, 2-aminoethoxydiphenylborate (2-APB), xestospongin C, isopropyl ␤-D-1-thiogalactopyranoside, glutathione, FITC-conjugated Pisum sativum agglutinin (FITC-PSA), and EGTA were from Merck; glutathione-Sepharose 4B was from GE Healthcare. Phorbol 12-myristate 13-acetate (PMA), 1,2-dioctanoyl-sn-glycerol (DAG) (catalogue number D5156), phosphatidic acid (PA), FIPI hydrochloride hydrate, 1,2-bis(2-aminophenoxy)ethane-N,N,NЈ,NЈ-tetraacetic acid tetrakis (acetoxymethyl ester) (BAPTA-AM), and A23187 were from Sigma; phosphatidylinositol 4,5-bisphosphate (PIP 2 ) and phosphatidylinositol 4-phosphate (PI4P) were from Avanti Polar Lipids, Inc. (Alabaster, AL); EGTA-AM and Fluo3-AM were from Invitrogen; [␥- 32 P]ATP and Chemiluminescence Reagent Plus were from PerkinElmer Life Sciences and Migliore Laclaustra SRL (Buenos Aires, Argentina); 1-butanol was from BDH Chemicals; anti-Rab3A was from Synaptic Systems (mouse monoclonal antibody, purified IgG clone 42.2); anti-ARF6 (mouse monoclonal anti-human ARF6, ab19871 or ab131261) and anti-PLD1 (rabbit polyclonal anti-human PLD1, ab10585) were from Abcam (Cambridge, UK); anti-SNAP25 (monoclonal mouse antibody, clone 71.1; conserved epitope), anti-RIM, and anti-complexin I/II were from Synaptic Systems; Cy-3-conjugated anti-rabbit and HRP goat-conjugated antimouse were from Jackson ImmunoResearch. The rabbit polyclonal anti-GST antibody (purified IgG) was purchased from…”
Section: Methodsmentioning
confidence: 99%
“…Controlled plasma membrane permeabilization has been used to gain access to the membrane fusion machinery required for exocytosis in several secretory cells (29,30). We used a well established streptolysin O (SLO) permeabilization protocol for studying acrosomal granule exocytosis (31)(32)(33)(34) that allows the incorporation of exogenous proteins, lipids, and ions into the cytosol. The extracellular calcium acts as an exocytosis inducer mimicking the opening of store-operated calcium channels.…”
mentioning
confidence: 99%
“…For the execution of the acrosome fusions additional Ca 2+ entry (in vitro by use of Ca 2+ ionophores, in vivo after zona binding) is required [9]. Diverse groups have shown that SNARE complex interacting proteins such as complexins [9,59, 60], dynamins [61], Rab 3A [62], synaptotagmins [63], multi-PDZ domain protein MUPP1, Calmodulin and CaMKIIalpha [64,65], Rab-2a, syntaxin binding proteins and Munc-18 (Tsai et al, unpublished results) have been discovered in sperm (see Fig. 5.2).…”
Section: Acrosome Exocytosismentioning
confidence: 99%
“…This is the site where the sperm binds to the zona pellucida and where the acrosome exocytosis as a response of that binding is inititated [46]. In that area within the aggregating lipid rafts MUPP1/CaMKIIα have been reported to interact with the trans ternary SNARE protein complex and this association functions as a fusion clamp [64,65]. (ii) The important factor in mouse sperm is the phosphorylated form of synaptotagmin, which appears to be important for preventing the acrosome exocytosis [63].…”
Section: Fig 52 Two Step Model For Snare Mediated Acrosome Exocytosmentioning
confidence: 99%